Making everyday choices : helping students in grades 2-5 practice the art of thinking - Josephson, Lin (Rowman & Littlefield, 2018)
This book focuses on helping children become self-reliant thinkers and decision-makers. The exercises are "practice runs" to be presented in a casual atmosphere where students share their thinking and receive educator guidance. Educators will learn that observing their students' thinking processes can provide insight into their decision-making.